Pyruvate‐lactate exchange and glucose uptake in human prostate cancer cell models. A study in xenografts and suspensions by hyperpolarized [1‐13C]pyruvate MRS and [18F]FDG‐PET. (14th July 2020) - van Heijster, Frits H.A.; Heskamp, Sandra; Breukels, Vincent; Veltien, Andor; Franssen, Gerben M.; Jansen, Kees (C).F.J.; Boerman, Otto C.; Schalken, Jack A.; Scheenen, Tom W.J.; Heerschap, Arend
Abstract : Reprogramming of energy metabolism in the development of prostate cancer can be exploited for a better diagnosis and treatment of the disease. The goal of this study was to determine whether differences in glucose and pyruvate metabolism of human prostate cancer cells with dissimilar aggressivenesses can be detected using hyperpolarized [1‐ 13 C]pyruvate MRS and [ 18 F]FDG‐PET imaging, and to evaluate whether these measures correlate. For this purpose, we compared murine xenografts of human prostate cancer LNCaP cells with those of more aggressive PC3 cells. [1‐ 13 C]pyruvate was hyperpolarized by dissolution dynamic nuclear polarization (dDNP) and [1‐ 13 C]pyruvate to lactate conversion was followed by 13 C MRS. Subsequently [ 18 F]FDG uptake was investigated by static and dynamic PET measurements. Standard uptake values (SUVs) for [ 18 F]FDG were significantly higher for xenografts of PC3 compared with those of LNCaP. However, we did not observe a difference in the average apparent rate constant k pl of 13 C label exchange from pyruvate to lactate between the tumor variants. A significant negative correlation was found between SUVs from [ 18 F]FDG PET measurements and k pl values for the xenografts of both tumor types. The k pl rate constant may be influenced by various factors, and studies with a range of prostate cancer cells in suspension suggest that LDH inhibition by pyruvate may be one of these. Our results indicate that glucose and pyruvate metabolism in the prostate cancer cell models differs from that in other tumor models and that [ 18 F]FDG‐PET can serve as a valuable complementary tool in dDNP studies of aggressive prostate cancer with [1‐ 13 C]pyruvate. Abstract : Differences in energy metabolism in murine xenografts of prostate cancer are found using hyperpolarized MR and PET. A significant negative correlation was seen between PET‐derived SUVs and 13 C‐MR‐derived k pl values for the xenografts of both tumor types. Standard uptake values (SUV) for [ 18 F]FDG were significantly higher for PC3 compared to LNCaP. Energy metabolism in prostate cancer cell models differ from other tumor models and [ 18 F]FDG‐PET can serve as a complementary tool in dDNP studies of aggressive prostate cancer with [1‐ 13 C]pyruvate.